Massas alimentícias sem glúten de farinhas formuladas à base de arroz e feijão - Nunes, Grasiella Moura (2020)
Pasta is a staple food in many countries. Typically, pasta products are produced using durum wheat, but currently, food manufacturers have started using other cereal grains to replace wheat. Therefore, the aim of the present study was to develop fresh gluten free pasta as a spaghetti based on polished rice flour and “black-eyed” beans using the Response Surface Methodology and the Desirability function. The physical and chemical characterization of the raw materials was carried out, afterwards a central composite rotational design (CCRD) was used resulting in 18 samples and the control pasta (100% rice flour) to investigate the effects of three independent variables: flour mixture rice and beans (X1) guar gum emulsifier (X2) and soy lecithin (X3), depending on the response variables: absorption rate, solubility rate, loss of solids, cooking time, weight gain, hardness and increase of volume. There were significant effects for the responses to absorption rate, optimal cooking time, weight gain, solubility and texture. The results of the centesimal composition of the flours showed that the bean flour has a protein content three times bigger than the rice flour. The mass defined by the Desirability function (R0) consisting of 83.15% rice flour, 16.85% bean flour, 7.0g guar gum, 0.45g soy lecithin was subjected to physical and chemical characterization, microbiological and sensory analysis and also the control pasta. The obtained data were treated by standard deviation, analysis of variance and the arithmetic average compared by the Tukey test (honestly significant difference). The R0 mass showed significant differences in the levels of minerals (iron, zinc, phosphorus and magnesium) and fat in relation to the control pasta. The microbiological analyzes carried out on the masses confirmed that the products presented satisfactory hygienic-sanitary conditions. Sensory analysis showed an acceptability rate of 74.6% and 79.1% for pasta R0 and control (with tomato sauce), and 69.5% and 74% for pasta R0 and control (without tomato sauce) showing good potential for consumption. There was a statistically significant difference in the control samples and in the optimized sample (R0) only in appearance and color. It was concluded that the elaborated pasta had good nutritional and acceptability results, therefore the preparation of spaghetti type pasta using proportions of rice flour and beans was satisfactory.